Protective effects of apocynin and melatonin on ovarian ischemia/reperfusion injury in rats - Çiğdem Kunt İşgüder; Murat Uysal; Özlem Koşar Can; Mine Kanat Pektaş; Akgül Arici; Velid Unsal (IMR Press, 2021)
Objective: This study aims to determine the protective effects of apocynin, a NADPH oxidase inhibitor, and melatonin, an endogenous anti-oxidant, in an animal model of ovarian ischemia/reperfusion (I/R) injury. Materials/Methods: Thirty-five female rats were randomly divided into five groups, namely group I (sham), group II (I/R), group III (I/R + 10 mg/kg apocynin), group IV (I/R + 20 mg/kg apocynin), and group V (I/R + 10 mg/kg melatonin). Ovarian tissue and serum superoxide dismutase (SOD) and catalase (CAT) activities and malondialdehyde (MDA) and protein carbonyl (PC) levels were measured. Ovarian histopathology was examined and Bax, caspase 3, and iNOS immunoreactivities were evaluated. Results: Preoperative apocynin and melatonin significantly increased SOD and CAT activities (P < 0.05, P < 0.05, P < 0.01, P < 0.01, P < 0.01, P < 0.05, P < 0.05, and P < 0.01, respectively, for both apocynin and melatonin). In addition, preoperative apocynin and melatonin significantly decreased the ovarian I/R injury score (P < 0.01 for both). Bax, caspase 3, and iNOS immunoreactivities were significantly lower in the I/R + 10 mg/kg apocynin and I/R + 10 mg/kg melatonin groups than in the I/R group (P < 0.01, P < 0.01, P < 0.01, P < 0.01, P < 0.05, and P < 0.01, respectively). Conclusions: Apocynin and melatonin are powerful anti-oxidant agents with considerable bioavailability and safety. Preoperative apocynin and melatonin administration might protect ovarian tissue from I/R injury after surgical adnexal detorsion.